Individual action, sharing scarce resources, sharing information? A study on how to effectively manage forest pests and diseases based on carbon trading - Shansong Wu; Yuntao Bai; Jiahao Li; Yueling Yang (PLoS ONE, 2025)
In recent years, forest pests and diseases have had a significant impact on forest ecosystems. To incentivize corporations to manage forest pests and diseases, the government provides certain carbon compensations to enterprises involved in this management. In the process of controlling forest pests and diseases, the modes of collaboration between the government and corporations are primarily categorized into three modes: independent action, scarce resource sharing, and information sharing. To determine the applicability of each relational mode, this paper constructs three differential game models and compares and analyzes the equilibrium results obtained from these modes. The research indicates that if the cost of government-managed forest pest and disease control is high and the benefits of such control are low, then the scarce resource sharing mode can offer the government the maximum benefit; conversely, the information sharing mode can provide the government with the greatest benefit. If the cost and benefits of corporate-managed forest pest and disease control are low, then the information sharing mode can offer corporations the maximum benefit; otherwise, the scarce resource sharing mode can provide corporations with the greatest benefit.